2003
DOI: 10.1242/jcs.00629
|View full text |Cite
|
Sign up to set email alerts
|

Rat aorta-derived mural precursor cells express the Tie2 receptor and respond directly to stimulation by angiopoietins

Abstract: Recent studies have implicated the Tie2 tyrosine-kinase receptor and its main ligands - angiopoietin-1 (Ang-1) and angiopoietin-2 (Ang-2) - as crucial regulators of mural cell recruitment during angiogenesis. Angiopoietin-mediated activation of Tie2 promotes perivascular mural cell assembly, but the mechanisms regulating this process are poorly understood because differentiated mural cells do not have the Tie2 receptor, which is reportedly expressed only in endothelial cells. There is also no direct evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 39 publications
1
63
0
Order By: Relevance
“…In addition, these experiments performed in serum-starved HBVP suggested that the effect of DA on Ang1 expression in pericytes is direct and is not the result of its actions on other growth factors. Furthermore, because there are reports indicating that up-regulation of Ang1 in pericytes stimulates migration of these cells (46,47), we examined the action of DA on HBVP migration (SI Results and Fig. S6).…”
Section: Da Treatment Promotes Mature Pericyte Coverage In Tumor Bloodmentioning
confidence: 99%
“…In addition, these experiments performed in serum-starved HBVP suggested that the effect of DA on Ang1 expression in pericytes is direct and is not the result of its actions on other growth factors. Furthermore, because there are reports indicating that up-regulation of Ang1 in pericytes stimulates migration of these cells (46,47), we examined the action of DA on HBVP migration (SI Results and Fig. S6).…”
Section: Da Treatment Promotes Mature Pericyte Coverage In Tumor Bloodmentioning
confidence: 99%
“…Ang1 promotes the assembly of the vessel wall by directly stimulating mural progenitor cells that express the Ang1 receptor Tie2 (Iurlaro et al, 2003;Howson et al, 2005) or by indirectly stimulating mural cells through the induction in endothelial cells of chemotactic factors such as CCL2 (Aplin et al, 2010). Interestingly, mural cell recruitment is also stimulated by Ang2 (Iurlaro et al, 2003), which was initially reported as an antagonist of Ang1 (Maisonpierre et al, 1997), but later recognized as a potential Tie2 activator whose agonist function was strongly influenced by contextual cues (Teichert-Kuliszewska et al, 2001). The migration and proliferation of mural cells is critically dependent on the p38 MAPK signaling pathway which can be activated by a number of angiogenic regulators including PDGFB and Ang1 (Yamaguchi et al, 2001;.…”
Section: Mechanisms Of Mural Cell Recruitmentmentioning
confidence: 99%
“…By treating the culture with vessel maturation factors, such as Ang-1 and MCP-1, increased MC recruitment was observed in this model. (Aplin et al, 2010;Iurlaro et al, 2003) However, since the model uses an organ part with multiple cell types, many other undefined cell types can also contribute to the network formation. It is difficult to isolate the contribution of each cell type in this model.…”
Section: Analytical Methods 341 In Vitro Modelsmentioning
confidence: 99%